Kedudukan Hukum Sistem Resi Gudang Sebagai Jaminan Kebendaan Serta Urgensi Peran Notaris Dalam Mewujudkan Pembiayaan Nasional Yang Berkeadilan (Analisis Putusan Mahkamah Agung Nomor 2654 K/PDT/2011) - Yohanes Wato Lewar; Whulan Putria Nanda; Seroja Dwina; Siti Kheirani Lubnayya; Nidia Aliza Kasnu Harda (Astha Grafika, 2026)
The Warehouse Receipt System (WRS) is a legal instrument developed to expand access to commodity-based financing, particularly for farmers and business actors in the agricultural sector, through the utilization of warehouse receipts as objects of collateral. Although governed by Law Number 9 of 2006 as amended by Law Number 9 of 2011 concerning the Warehouse Receipt System, its implementation still faces various issues related to the legal certainty of the position of warehouse receipts as proprietary collateral and legal protection for the parties involved. This research aims to analyze the legal arrangements of the Warehouse Receipt System as a collateral institution, the forms of legal protection for the parties, and its application in Supreme Court Decision Number 2654 K/Pdt/2011. This research employs a normative juridical research method with statutory, conceptual, and case approaches, analyzed descriptively-analytically using primary, secondary, and tertiary legal materials. The research results indicate that normatively, the Warehouse Receipt System has provided a legal basis for the use of warehouse receipts as objects of proprietary collateral. However, its implementation still faces various obstacles, including the suboptimal application of the principles of legal certainty and legal protection, infrastructure limitations, low literacy among business actors, and the lack of uniform acceptance of warehouse receipts as collateral by banking institutions. Supreme Court Decision Number 2654 K/Pdt/2011 demonstrates that the rights of creditors holding warehouse receipt collateral have not received optimal protection when the collateral object becomes a dispute. Therefore, it is necessary to synchronize regulations with national collateral laws, strengthen the warehouse receipt registration mechanism, and optimize the authority of notaries in drafting deeds of collateral imposition.